Construction and validation of an instrument for physical therapy assessment and functional classification in the biopsychosocial model of the International Classification of Functioning, Disability and Health (ICF) for hospitalized HIV patients (Fisioterapia e Pesquisa, 2023)
The human immunodeficiency virus (HIV)is responsible for the compromise of the immune systemand a high number of hospitalizations. Consideringthe biopsychosocial (BPS) context of the individual,the International Classification of Functioning, Disabilityand Health (ICF) provides the maximum description ofa health condition and the impact of interventions andservice delivery for the physiotherapeutic process. The aimof this study was to build and validate a physical therapyassessment and functional classification instrument basedon the ICF for hospitalized members of the HIV community.This is an observational, cross-sectional, and descriptivestudy based on the analysis of demand, elaboration, and improvement of the instrument and its validation withthe consensus of a experts committee of physical therapists;they evaluated 58 items and the classification codes resulted in0.858 overall Kappa value=strong agreement between assessments,all statistically significant (p-value<0.05). The final version of theinstrument included 36 items, all with Kappa coefficient >0.80.The constructed instrument is valid for the evaluation and functionalclassification in the ICF model for hospitalized members ofthe HIV community, contributing to the physical therapy clinicalpractice in the hospital environment.